Factors Associated with Mental Health in ADHA and Non ADHA in South Sumatera - Fathiya, Iska; Sitorus, Rico Januar (Universitas Nusa Cendana, 2023)
Mental health is a state of physical and mental health in which a person is able to live daily life with a sense of security and peace. Children with HIV/AIDS positive have a double burden compared to children with HIV/AIDS negative where it greatly affects the mental state of a child. This study aims to factors associated with mental health in ADHA and Non ADHA in South Sumatera. The study design used a cross sectional with a sampling technique using cluster sampling. Locations in this study include areas in South Sumatera like Palembang City, Prabumulih City, and OKI. Data collection was carried out from April – May 2022 by interviewing through the Self Reporting Questionnaire (SRQ) mental health questionnaire. The research sample was 61 people with criteria for children aged 5-18 years. Statistical analysis used the Chi Square test with a significance level of = 0.05. The results showed that parental income (p=0.599) and nutritional status (p=0.186) were not related to mental health, while history of chronic disease (p=0.037), parental completeness status (p=0.037), and HIV/AIDS status (p=0.008) associated with mental health. Increased monitoring of mental health needs to be optimized in order to reduce the incidence of mental health disorders in children.